„Niebiańscy orędownicy” – w kręgu kultu świętych patronów rodu Sobieskich i ich peregrynacji - Pietrzak, Jarosław (Acta Universitatis Lodziensis. Folia Historica, 2013)
The purpose of this article is to present the forms devotion used by the Sobieski family to venerate Saint James the Greater and Saint Hyacinth and incidentally also Saint Dacian and Saint Crescentia. The family forefathers – Stanisław and Jan Sobieski – were Protestants and therefore did not venerate saint patrons. Marek Sobieski’s conversion to Catholicism, brought about by many reasons e.g. promotion prospects and Jan Zamoyski’s influence, motivated the family to take up patron saints to intercede with God on their behalf. The pilgrimage to Santiago de Compostela made by Jakub Sobieski initiated the veneration practices by the family members. This article discusses the enigmatic voyage that Jakub Ludwik Sobieski supposedly made and argues that it was only a popular manner of picturing the patron saints leading souls to salvations. Founding churches, votive altars and lamps and pilgrimages as well were expressions of Saint Hyacinth’s cult. This cult encompassed not only Kraków but also Złoczów, Zółkiew and Pomorzany, cities owned by the Sobieski family. It is also important to emphasise John III Sobieski’s efforts to proclaim St Hyacinth the saint patron of Poland as a thanksgiving for the victorious Battle of Vienna. The article includes references to archival sources, topical literature as well as literary and iconographic works.